Child living arrangements following separation and mental health of parents in Sweden. (April 2020) - Fritzell, Sara; Gähler, Michael; Fransson, Emma
Abstract: Father involvement and joint physical custody in post-separation families are increasingly common. In Sweden, 35 percent of the children of separated parents live equally much with both parents. Since parenthood is gendered, the associations between child living arrangement and parental health may vary between women and men. This study analyzes the association between children's living arrangement and mental health of parents, and how this interacts with material and social circumstances. Drawing on The Swedish Survey of Living Conditions (ULF) 2008–2013, the association between child living arrangements and mental health (worry/anxiety) of parents in five family structures: two biological parents, reconstituted with joint or main/sole custody arrangements, single with joint physical custody, and single with main or sole custody, were analyzed. Data on 9, 225 mothers and fathers with resident children aged 0–17 were analyzed by logistic regressions for average marginal effects adjusting for socio-demographic, socio-economic and social factors. Analyses of interaction effects were made using the synergy index. Substantial family type differences were found in mental health between two biological parent family and all other family types for mothers, and two biological parent family and single parents for fathers. For the single mothers, the higher risk for worry and anxiety was still found following controls for socioeconomic factors. For fathers, the only differences that remained following control for socioeconomic factors was that of single fathers with children in joint physical custody. Interaction effects were found for the combination of single motherhood and non-employment, indicating a higher risk of mental health problems for single mothers (both with joint and sole custody), than would be expected from a simple addition of these exposures, suggesting that this is a vulnerable group. The results indicate that joint custody is associated with higher risk for worry and anxiety for the parents, especially for mothers both re-partnered and single, but also for single fathers. Highlights: Economic and social conditions explain part of the differences in mental health. Single mothers lacking employment is a particularly vulnerable group. Shared residence is associated with higher risk for worry and anxiety in parents.